Finite Element Analysis of a Road Divider for Impact Testing and Material Selection. Issue 1 (1st February 2023) - Patwardhan, Devendra; Ghorpade, Ratnakar R.; Karandikar, Ketan V.
Abstract: Road divider is one of the most important things which needs to be worked on because many times vehicles are hit on the road divider which results in serious injury or death of the person because generally road dividers are made from concrete, and concrete does not have impact force reducing capacity. On the other side, composite materials like Bamboo-based polymer composite, foamed PVC-based composite and Jute fiber reinforced composites have a higher impact force absorbing capacity. The primary objective of this research is to select a material that is suitable to absorb the impact of the car and not to transfer any forces back in to the car, which will further avoid or reduce the overall impact of the injury to the passengers.